Evaluation of Bridge Coffee Customer Expexrience - Hermawan, Devina; Iskandar, Budi Permadi (Journal of Business and Management, 2016)
Abstract. Along the years, we can not deny that coffee shop become a fast-growing business in Indonesia especially in urban city such as Jakarta, Bandung, Medan, Surabaya, and other cities. There is a really huge market this sector since drinking coffee is not longer a necessity but lifestyle. Bridge Coffee is on of those coffee players which produce premium roasted Indonesian coffee beans and other beverages for cafes, restaurant, corporation, and especially for end-customer. They are currently planning to open their first coffee shop in Bandung, which they named it Bridge Coffee Boutique and Dining. Coffee shop is a very competitive business, and attracting new customers is a consistent challenge. One of the best ways to attract new customers to Bridge Coffee Boutique and Dining is to offer something of value to change their "normal" behavior and encourage them to try something new. Therefore, this research has the objective to examine experiential marketing program from Bridge Coffeeâ€™s potential customers and give recommendation to Bridge Coffee Boutique and Dining on the things the should do. To gather the data, focus group discussions were done three times. The result of this study shows that the customer already recognized some uniqueness of experience in Bridge Coffee Boutique and Dining. It highlights the coffee gallery, which show many information about coffee, coffee beans and coffee equipment showcase as the first experience that given to visitor. Another result is that Bridge Coffee Boutique and Dining overall service admitted higher than average compared with other cafe or restaurant. Therefore, the recommendation for Bridge Coffee is to provide the customer with a simple customization for their order to create a really pleasent experience.Â Keywords: Coffee, Coffee shop, Focus group discussion, Experiential marketing, Experience